Data Architecture Standard Review Component for SQLite Database Manager - Lima Torres, Sandra (2021)
Concern for the quality of software-based systems has grown as software is integrated into every aspect of our lives. With the increase in the number of users and the data stored, more robust and secure databases are necessary. Quality control testing has progressed systematically from manual to automated applications. The Information Technology for Defense Company has the Center for Quality Standards and Security in charge of certifying and technically evaluating computer products, guaranteeing their quality. Currently the database review process in the SQLite manager is manual, making this process difficult, where there may be a margin of error due to the amount of checks that must be reviewed. The present work aims to develop a data architecture review component for the SQLite management server. For this, a study of a homologous database management system is carried out, the tools for testing existing databases and how a database architecture standard is formed. Functional tests are carried out on the component to verify its correct operation. Finally, a component integrated o the Zeolides framework is obtained, capable of automatically checking the architecture of the databases of the SQLite manager in the computer applications developed in the company.